Improving Students' IPAS Learning Outcomes through a Mind Mapping-Assisted Collaborative Creativity Learning Model - Ni Kadek Verawati; I Gusti Ayu Tri Agustiana; Rendy Setyowahyudi (Universitas Pendidikan Ganesha, 2026)
IPAS (Natural and Social Sciences) learning plays an important role in developing students’ abilities through observation, experimentation, and problem solving. Students’ learning outcomes are still not optimal because learning tends to be teacher centered, so students’ engagement, collaboration, and creativity have not developed maximally. This study aims to analyze and examine the effect of the collaborative creativity model assisted by mind mapping on students’ IPAS learning outcomes. This study uses a quantitative approach with a quasi experimental type and a non equivalent post-test only control group design. The research subjects consisted of 51 elementary school students selected through a random sampling technique. Data were collected using an objective test and analyzed using descriptive and inferential statistics with the help of SPSS. The analysis results show a significance value of 0.000 < 0.05, which confirms that the implementation of the collaborative creativity model assisted by mind mapping has a significant effect on improving students’ IPAS learning outcomes. The conclusion of this study is that the integration of a collaborative model and visual media is able to increase students’ active engagement, creativity, and conceptual understanding more optimally. The implication of this study shows that the collaborative creativity model assisted by mind mapping can be used as an alternative innovative learning strategy that is effective in improving the quality of IPAS learning in elementary schools and supporting the development of students’ 21st century skills.